Horizontal connections of intellectual property right as a sub-branch of civil law (on the example of correlation with the institute of unfair competition) - Ivanova, Diana V. (Journal of the Belarusian State University. Law, 2019)
Horizontal connections of intellectual property right as a sub-branch of civil law with the institute of unfair competition are considered in the paper. To determine the effect of horizontal connections on the formation of the intellectual property rights system structural links between the institutions and norms are identified and taken into account and behaviour of components and the system as a whole are predicted. In their interaction, they are designed to ensure the necessary balance between the interests of consumers, rights owners of intellectual property rights, their competitors. The conclusions that some provisions of unfair competition institution are restrictions on freedom of the realization of the exclusive right by subjects of intellectual property law are drawn.
Keywords: civil law; exclusive right; intellectual property law; structural principle; system of law; unfair competition